Pengaruh Financial Teknologi, Pengelolaan Keuangan dan Modal Sosial Terhadap Kinerja UMKM di Sentral Grosir Cikarang (SGC) - Nurjanah; Carolyn Lukita; Ihsan Nasihin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The study aimed to analyse the impact of financial technology, financial management, and social capital on SME performance. Several factors influence SME performance, including internal funding and external factors. Issues to address include underutilisation of financial technology, ineffective financial management, and lack of utilisation of social capital. This quantitative study collected data via a questionnaire from 60 SME operators using purposive sampling. Data analysis employed multiple linear regression assisted by SPSS. Findings revealed that financial technology, financial management, and social capital positively influence SME performance. This is due to the effective utilisation of technological advancements in business operations significantly enhancing SME performance. Improved financial management enables SMEs to seek funds selectively and use them efficiently. Similarly, building social capital facilitates SME operators' adaptation to their business environment, thereby enhancing SME performance. Recommendations for future research include expanding the scope of study variables, and SMEs should maintain and enhance the factors of financial technology, financial management, and social capital influencing SME performance. With financial technology, SMEs can access financial services more easily, utilise financial management for better record-keeping and calculation, and build social capital to develop their businesses.